Water remediation and antibacterial characteristics of CdO, graphene oxide and reduced graphene oxide blended CdO nanoparticles – A comparative study - N. Manjula; A.R. Balu; N. Arunkumar; S. Chitra Devi; M. Sriramraj; V. Rajamani; A. Vinith (Chemistry of Inorganic Materials)
The antibacterial and water remediation capabilities of CdO (CO), graphene oxide blended CdO (GCO), and reduced graphene oxide blended CdO (rCO) nanoparticles produced using one-pot green synthesis and chemical precipitation techniques have been compared. XRD, SEM, TEM, BET, XPS, UV–Vis–NIR, PL, and FTIR techniques were employed to characterise the produced NPs. CO, GCO, and rCO all have a cubic crystal structure and tend to grow in a (1 1 1) direction. The scanning electron micrographs showed that the grains were evenly distributed. Oxidation states of Cd and O in rCO sample were Cd2+ and O2− from XPS analysis. Cd–O stretching vibration occurs at 668, 556 and 472 ​cm−1 for CO, GCO and rCO, respectively. Optical absorption of CO increased with GO and rGO blending. Blending GO reduced CO's band gap from 2.44 to 2.41 and rGO lowered it to 2.39 ​eV. The photodegradation effectiveness of CO, GCO and rCO against methyl orange (MO) dye under visible light was 80.9, 86.6 and 95 ​% after 90 ​min. Bacterial growth inhibition quality of CO increased with GO/rGO blending and they show better resistance against B. subtilis (gram ​+ ​ve) than E. coli (gram –ve) bacteria. Compared to GCO, rCO exhibited better photocatalytic and antibacterial properties signifying its potential for water remediation and antibacterial applications.